Right-Wing Populism in Central Europe: Hungarian Case (Fidesz, Jobbik). / Populismo de derecha en Europa central: caso húngaro (Fidesz, Jobbik). - ILIKOVA, LILIA; TUSHEV, ANDREY (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The migration crisis of 2015 in Europe had a huge impact on the political field of the European Union. The migration crisis has caused an increase in xenophobia in countries receiving migrants, while at the same time giving a powerful impetus to the revival of nationalism. The Visegrád group countries – the Czech Republic, Slovakia, Poland and Hungary – took a particularly harsh position on migration flows and the EU migration regulations. Among these countries, Hungary stands out for its consistent political position, which is resistant to criticism from outside, including from the structures of official Brussels.RESUMEN La crisis migratoria de 2015 en Europa tuvo un gran impacto en el ámbito político de la Unión Europea. La crisis migratoria ha provocado un aumento de la xenofobia en los países receptores de migrantes, al mismo tiempo que ha dado un poderoso impulso al resurgimiento del nacionalismo. Los países del grupo Visegrád (República Checa, Eslovaquia, Polonia y Hungría) adoptaron una posición particularmente dura sobre los flujos migratorios y las regulaciones migratorias de la UE. Entre estos países, Hungría se destaca por su posición política consistente, que es resistente a las críticas del exterior, incluso de las estructuras oficiales de Bruselas.